The Ideal of the Bishop and the Venetian Patriciate: c. 1430–c. 1630 - Logan, Oliver (The journal of ecclesiastical history, 1978)
Venetian religious literature of the Renaissance period presents an amorphous picture to the historian; there were few recurrent preoccupations among Venetian religious writers and they used a wide variety of theological styles. The topic of the officium episcopi, the bishop's duties and rule of life, did however recur with some frequency. There was, indeed, a considerable volume of literature on this subject in Catholic Europe as a whole between the Conciliar era and the post-Tridentine period. The best known, almost the only widely known Italian example of the genre is the work of a Venetian: the De officio episcopi of Gasparo Contarini. Other Venetian writings on this theme have been barely studied, however, although in some cases they are subtler and more redolent of spirituality, if less explicit, than Contarini's work. It may well be that Venetians, over a period of a century and a half, made a particularly important contribution to the genre and since the Venetian patriciate produced a large number of bishops (the major bishoprics of the Venetian Terraferma were normally held by Venetian nobles) this would not be altogether surprising. It should be said, however, that even in this genre of religious literature it is difficult to point to a specifically Venetian tradition or to any particular continuity of themes; to take the case of Gasparo Contarini, a search for the Venetian antecedents of his ideas yields rather sparse fruits.